2013
DOI: 10.1007/s10072-013-1391-z
|View full text |Cite
|
Sign up to set email alerts
|

Nociception and autonomic nervous system

Abstract: The International Association for the Study of Pain (IASP) defines pain as ''an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage''. Pain may also be experienced in absence of noxious stimuli and together with temperature and other bodily feelings constitute the interoception redefined as the sense of the physiological condition of the entire body, not just the viscera. The main characteristic of these feelings is the affective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 75 publications
2
41
0
Order By: Relevance
“…Another finding of our study is that ESC values in patients with FM were significantly diminished on the dominant hand, suggesting a nonsymmetrical severity of autonomic dysfunction, considering that no clinical sign or symptom of carpal tunnel syndrome was noted in the patients at inclusion. The insula is well known to encode both the intensity and the laterality of painful and nonpainful thermal stimuli. A lateralization in autonomic dysfunction has also been shown in pathological conditions like ischemic stroke and is usually contralateral.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of our study is that ESC values in patients with FM were significantly diminished on the dominant hand, suggesting a nonsymmetrical severity of autonomic dysfunction, considering that no clinical sign or symptom of carpal tunnel syndrome was noted in the patients at inclusion. The insula is well known to encode both the intensity and the laterality of painful and nonpainful thermal stimuli. A lateralization in autonomic dysfunction has also been shown in pathological conditions like ischemic stroke and is usually contralateral.…”
Section: Discussionmentioning
confidence: 99%
“…The NTS and lamina I provide dense connections to the parabrachial nucleus (PBN), the main integration centre for all homeostatic afferent activity (Cortelli et al, 2013). These connections then transmit to both the periaqueductal gray area (PAG) and the hypothalamus.…”
Section: Typical Interoceptive Pathways and Connectionsmentioning
confidence: 99%
“…The autonomic nervous system plays a role in the anticipation of and response to pain (30). Through its integration with structures in the upper brainstem, hypothalamus, anterior cingulate cortex, insula, and amygdala, the autonomic nervous system integrates bodily sensation with emotion and generates homeostatic autonomic responses (30). Lush et al (31) reported that women with fibromyalgia who completed a mindfulness-based stress-reduction program had decreases in basal sympathetic tone.…”
Section: Autonomic Nervous System Process Changesmentioning
confidence: 99%